RELAÇÕES ENTRE PARÂMETROS CLÍNICOS E SÉRICOS DE DOENÇAS/ALTERAÇÕES INFLAMATÓRIAS CRÔNICAS E DOENÇAS PERIODONTAIS EM ADOLESCENTES. - FRANCO, Mayra Moura (2016)
Periodontal disease (PD) is an inflammatory disease, which involves protection and support tissues of the teeth and is related to an impaired immune host-response. The possible associations of periodontal disease with chronic systemic diseases and other diseases have been of great interest in recent years. It is plausible that these associations are the result of common and non-causally related risk factors and even though these relationships may occur bidirectionally. There are several possible associations with periodontal disease: cardiovascular diseases, diabetes mellitus type 2, chronic kidney disease and rheumatoid arthritis. In this context, the metabolic syndrome (MS) and its components have also been associated with periodontal disease, however, the mechanisms that link these alterations still need to be elucidated. In turn, NGAL (neutrophil gelatinase-associated lipocalin), also known as lipocalin-2, is a glycoprotein of the lipocalin family (small extracellular proteins), important in the defense of the body against various diseases and has been studied as a biomarker for systemic diseases such as acute and chronic kidney disease, cardiovascular diseases and inflammatory bowel diseases. In periodontal tissues, few studies have evaluated NGAL and these relationships are still not well established. Most of these studies that studied the possible association of periodontal diseases and systemic diseases and inflammatory disorders were performed in adult patients. Therefore, studying these relationships in adolescents may help to understand the mechanisms and progression of these changes. Thus, the Chapter I, Association of components of metabolic syndrome with periodontal disease parameters in adolescents, evaluated the association of the components of metabolic syndrome and periodontal disease parameters in adolescents aged 17-18 years. This is a representative observational study of students of public schools in São Luís - MA, with random sampling in 3 stages (school, class and students) from January 2014 to July 2016 (n = 365). Probing depth (PD) and bleeding on probing (BOP) were measured at six sites per teeth, except third molars. The variables components of MS, blood pressure, high-density lipoprotein cholesterol (HDL-C), triglycerides, waist-hip ratio and body mass index (BMI) were analyzed in association with the extent of periodontal disease (BOP and PD) and assessed as discrete variables (number of sites with BOP and the number of sites with PD ≥ 4 mm). First, a bivariate analysis was performed between components of metabolic syndrome and each periodontal outcome. Next, the models were adjusted for sex, adolescent´s skin color, maternal education level and household income. The estimated coefficients were calculated in Poisson regression models and expressed as the means ratio (MR) and 95% confidence intervals (95% CI), with significance level of 5% (α = 0.05). In adjusted models HDL-C (MR 1.20, p <0.001; MR 1.47, p <0.001), triglycerides (MR 1.11, p = 0.001; MR 1.54, p <0.001), diastolic blood pressure (MR 1.84, p <0.001; MR 1.76, p <0.001), waist-hip ratio (MR 12.07, p <0.001; MR 5.86, p = 0.024) and BMI (MR 1.67 p <0.001; MR 2.33, p <0.001) were associated with the number of sites with BOP and with the number of sites with PD ≥ 4 mm, respectively. Thus, components of the metabolic syndrome, in particular those linked to inadequate dietary patterns, are individually and independently associated with and periodontal disease activity and tissue destruction in adolescents. And Chapter II, Serum NGAL levels and periodontal disease parameters in adolescents, verified the relationship between serum levels of NGAL and periodontal disease parameters in adolescents aged 17 and 18 years. This is a representative observational study of students of public schools in São Luís - MA, with random sampling in 3 stages (school, class and students) from January 2014 to July 2016 (n=281). The following periodontal parameters were evaluated: bleeding on probing (BOP), probing depth (PD) and clinical attachment level (CAL) at six sites per teeth, except third molars. The mean of serum NGAL levels of adolescents were compared using the Independent Student‘s t-test according to the following parameters: 1) bleeding on probing (the presence of at least 15% of sites with BOP); 2) PD (the presence of at least one tooth with PD ≥ 4 mm in one or more sites); 3) CAL (the presence of at least a tooth with CAL ≥ 4 mm in one or more sites). Serum NGAL levels were correlated to the extent of periodontal disease using the Pearson‘s coefficient (Pearson‘s linear correlation) according to the following parameters: the number of sites with bleeding on probing, the number of sites with PD ≥ 4 mm and the number of sites with CAL ≥ 4 mm. In addition, serum NGAL levels were analysed in association with the extent of periodontal disease (BOP, PD and CAL) and assessed as discrete variables. First, a bivariate analysis was performed. Next, the models were adjusted for sex, household income and smoke. The estimated coefficients were calculated in Poisson regression models and expressed as the means ratio (MR) and 95% confidence intervals (95% CI). The significance level applied in all analyses was 5% (α = 0.05), and data were analysed using Stata software (version 14.0). The mean of serum NGAL levels were significantly higher in adolescents who presented: 15% or more sites with BOP (p = 0.002); at least one tooth with PD ≥ 4 mm (p <0.001); at least one tooth with CAL ≥ 4 mm (p <0.001). NGAL had significant and positive correlations with the following periodontal parameters: the number of sites with bleeding on probing (r = 0.188; p = 0.001), the number of sites with PD ≥ 4 mm (r = 0.250, p = 0.001), and number of sites with CAL ≥ 4 mm (r = 0.303, p <0.001). In the multivariate analysis, the highest tertiles of NGAL were significantly associated with BOP (MR=1.52, CI=1.37-1.69, p < 0.001), PD (MR=1.76, CI=1.38-2.24, p < 0.001) and CAL (MR=2.93, CI=2.05-4.19, p < 0.001). Systemic inflammation, here marked by higher levels of NGAL, is associated with periodontal disease parameters in adolescents. In this sense, periodontal disease may be a clinical marker/condition in the oral cavity reflecting systemic inflammation and/or future risk for chronic diseases.